To your eternity. 14 - Oima, Yoshitoki (Kodansha Comics, 2021)
In a new age, Fushi befriends a teenager named Yuki. In the comforting safety of Yuki's home, Fushi gathers his comrades one last time. As the days pass, Fushi also meets a descendent of Hayase named Mizuha. He laughs, feasts, and ponders what new emotions and encounters await. Before long, however, a troubling encounter sends ripples of doubt through his quiet life.